Impact of Custom Duties, Energy Import and Government Health Spending on Greenhouse Gas Emission in Thailand - Srimarut, Thammarak; Mekhum, Witthaya (International Journal of Energy Economics and Policy, 2020)
Greenhouse gas emission has become a great problem throughout the world and many countries are facing serious outcomes in this regard. There may be various factors that may affect the emission of greenhouse gases but in this study the author has discussed the impact of custom duty, energy imports and government health spending on greenhouse gas emission. Data was collected from Thailand for research purpose for period of 28 years. Several tests such as unit root test, co-integration test and ARDL test in long and short run have been applied on the collected data for various purposes. The results of these tests indicate that the impact of three independent variables, custom duty, energy imports and government health spending is significant while the impact of only one control variable, energy consumption is significant in regard of greenhouse gas emission. After the detailed discussion of results, the author has mentioned some important implications related to this study in various contexts. These implications revolve around one common point i.e. reduction in greenhouse gas emission. In the last, the limitations associated with the study have also been discussed. Keywords: Custom Duties, Energy Import, Government Health Spending, Greenhouse Gas Emission JEL Classifications: H51, K32 DOI: https://doi.org/10.32479/ijeep.10722